Photoisomerization and thermal isomerization of ruthenium aqua complexes with chloro-substituted asymmetric bidentate ligands. Issue 4 (15th January 2019) - Hirahara, Masanari; Goto, Hiroki; Yamamoto, Rei; Yagi, Masayuki; Umemura, Yasushi
Abstract : Introduction of a chloro substituent to the bidentate ligand of ruthenium aqua complexes enhanced photoisomerization and thermal back-isomerization. Abstract : A series of ruthenium complexes with chloro-substituted bidentate ligands, proximal-[Ru(tpy)(Cl-pyqu)L] n + [ n = 1 for L = Cl, and n = 2 for L = OH2, tpy = 2, 2′;6′, 2′′-terpyridine, pyqu = 2-(2′-pyridyl)quinoline] were synthesized and their reversible photoisomerizations and thermal isomerizations were investigated experimentally. The crystal structures of the complexes indicated that introduction of a chloro substituent at the 4- or 4′-position of the pyqu ligand did not change the structure around the metal center from that of the non-substituted complex, proximal-[Ru(tpy)(pyqu)L] n + . In contrast, the 6′-substituted complexes had sterically hindered environments around the metal center. The ruthenium aqua complexes showed reversible photoisomerization between the proximal and distal isomers. The quantum yield for photoisomerization of the 6′-substituted ruthenium aqua complex was almost twice as large as those of the other derivatives. This is explained by weakening of the ligand field on the ruthenium center by introduction of a chloro substituent at the 6′-position. Thermal back isomerization from the distal isomer to the proximal one was observed for the 6′-substituted complex, but such reactions were not observed for the other derivatives. The steric hindrance in the 6′-substituted aqua complex enhanced both thermal isomerization and photoisomerization.